2015
DOI: 10.1038/srep16360
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Metrology: Surpassing the shot-noise limit with Dzyaloshinskii-Moriya interaction

Abstract: Entanglement is at the heart of quantum technologies such as quantum information and quantum metrology. Providing larger quantum Fisher information (QFI), entangled systems can be better resources than separable systems in quantum metrology. However the effects on the entanglement dynamics such as decoherence usually decrease the QFI considerably. On the other hand, Dzyaloshinskii-Moriya (DM) interaction has been shown to excite entanglement. Since an increase in entanglement does not imply an increase in QFI,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…An interesting point here is that although resulting in different systems, therefore different corresponding density matrices and different entanglement values, inhomogeneous magnetic field and DM interaction excite the QFI in the same way. Exhibiting first a sudden increase and then a slow decrease with respect to increasing B, b or D, the QFI of ferromagnetic chain remains well larger than that of antiferromagnetic chain, surpassing the shotnoise level, in accordance with our recent findings for the XXX model including only DM interaction [35]. By fixing the temperature at T = 0.7, we explore the effects of DM interaction and magnetic fields together, and homogeneous and inhomogeneous magnetic fields together in QFI in Fig.2.…”
Section: Introductionsupporting
confidence: 92%
“…An interesting point here is that although resulting in different systems, therefore different corresponding density matrices and different entanglement values, inhomogeneous magnetic field and DM interaction excite the QFI in the same way. Exhibiting first a sudden increase and then a slow decrease with respect to increasing B, b or D, the QFI of ferromagnetic chain remains well larger than that of antiferromagnetic chain, surpassing the shotnoise level, in accordance with our recent findings for the XXX model including only DM interaction [35]. By fixing the temperature at T = 0.7, we explore the effects of DM interaction and magnetic fields together, and homogeneous and inhomogeneous magnetic fields together in QFI in Fig.2.…”
Section: Introductionsupporting
confidence: 92%
“…Sharma et al studied entanglement sudden death and birth [7] and entanglement dynamics [8] of qubit-qutrit systems, also of Werner states [9] and qubit-qutrit systems with x-component DM interaction [10]. Because, unlike entanglement mea-sures, quantum Fisher information (QFI) is not an entanglement monotone that it can be increased via local operations and classical communications [11], we asked whether it can be excited via DM interaction too, and showed that it can be [12,13]. Bound entanglement (BE) [14] and its activation are among the most interesting phenomena in quantum mechanics [15,16].…”
Section: Introductionmentioning
confidence: 98%
“…Enhancement of sensitivity and precision in quantum metorology [14,15] is an important aspect which has been achieved by using many techniques, spin squeezing is one of these. Squeezing of spins play an important role for quantum metrology and magnetometery to improve the sensitivity and precision because of its ability to reduce the quantum noise [16][17][18][19][20]. Early experimental manifestations of spin squeezing is demonstrated in varieties of physical systems such as, in entangled ion trap systems [21], in Bose-Einstein condensate (BEC) through repulsive interactions [22], measurements by partial projection [23], squeezing of huge ensemble of atoms in cavities through light-matter interaction to produce atomic clocks [24][25][26][27][28][29][30], gravitational interferometers [31][32][33] and in many qubit systems [34][35][36].…”
Section: Introductionmentioning
confidence: 99%